Optimal Cost Overruns: Procurement Auctions and Renegotiation - Fabian Herweg; Marco A. Schwarz (Center for Economic Studies and ifo Institute (CESifo), 2016)
Cost overrun is ubiquitous in public procurement. We argue that this can be the result of a constraint optimal award procedure when the procurer cannot commit not to renegotiate. If cost differences are more pronounced for more complex designs, it is optimal to fix a simple design ex ante and to renegotiate to a more complex and costlier design ex post. Specifying a simple design initially enhances competition in the auction. Moreover, the procurer cannot benefit from using a multi-dimensional auction, as the optimal scoring rule depends only on the price.
Keywords: D44; D82; H57; 330; auction; cost overrun; procurement; renegotiation